Effects of Arc-Shaped Partitions in Corners of A Shallow Cavity on Natural Convection - Gürtürk, Mert; Öztop, Hakan Fehmi; Selimefendigil, Fatih; Al-salem, Khaled (My University, 2019)
In this study, a numerical analysis carried out to determine the effects of arc-shapedpartitions in corners of a shallow cavity on heat transfer which is natural convectionand fluid flow. Partitions are accepted as conductive and two different partitions materialsare chosen as wood and aluminum. The finite volume approach is used to discretize thegoverning equations for Rayleigh numbers (Ra) and shape ratio of the arc-shaped partition.It is found that arc-shaped partitions have effect on characteristic parameters of fluid flowand heat transfer. Specially, aluminum arc-shaped partition affects the average heat transferenhancement, because it has high heat transfer coefficient. Also, possibilities of occurringdead regions are examined and streamlines obtained for without partitions and highRayleigh numbers which are Ra=105 and Ra=106 show that dead regions occur in cornersof the shallow cavity. Results obtained from the analysis using partitions and consideringdifferent Rayleigh numbers and partition materials show that using partition which is arcshapedprevent occurring dead regions.
Keywords: Fizik; Uygulamalı; Termodinamik; Fizikokimya